Utilizarea indicelui Timmy la evaluarea cercetării științifice - Mocan, Vladimir (CEP USM, 2024)
Evaluation has become an essential part of the research process, critical to measuring policy objectives, making decisions about program budgets, project selection, funding awards and career development. The article analyzes the issue of evaluating scientific research. Evaluation should recognize both quantitative and qualitative contributions, taking into account the objectives, discipline and institutional context. There is no single perfect system of evaluation and respect for diversity is crucial. Capitalizing on international experience, primarily European, should be part of the evolution of the system in the Republic of Moldova. The aim should be to introduce new indicators (or adapt old ones) that help to better disclose quality and that are transparent and fit the purpose of the assessment, while maintaining a concrete system based on the principle of objectivity. All knowledgeable stakeholders should be involved in the transition to new research evaluation systems. In this sense, the use of an indicator for the evaluation of national scientific organizations is proposed.
THE USE OF THE TIMMY INDEX IN EVALUATING SCIENTIFIC RESEARCH
Keywords: evaluation; research; measurement; Open Science; Timmy index.; evaluare; cercetare; măsurători; Știință deschisă; indicele Timmy.